Return migration patterns of porbeagle shark (Lamna nasus) in the Northeast Atlantic: implications for stock range and structure. (10th January 2017) - Biais, Gérard; Coupeau, Yann; Séret, Bernard; Calmettes, Beatriz; Lopez, Rémy; Hetherington, Stuart; Righton, David
Abstract : During two surveys in 2011 and 2013, we deployed pop-up satellite archival tags (PSATs) on subadult or adult porbeagles at the Bay of Biscay shelf break. We collected data that enabled the reconstruction of nine migrations (eight females, one male) that uncover the large spatial extent of these sharks in the Northeast Atlantic. The mean duration of each deployment was 292 d, with four reaching 365 d. The reconstructions show that, after migrations that extended up to 2000 km away from the point of release, the tagged porbeagles returned to their location of tagging. All the reconstructed migrations followed the same general pattern of a migration away from the Bay of Biscay in late summer, and a return in spring the following year. The total distance of the migrations was estimated at 5000–13 000 km for PSATs deployed for a full year (n = 4), with examples of migration to the Arctic Circle, southward to Madeira and westward to the mid-Atlantic Ridge. The observed site fidelity to the Bay of Biscay and the common migration pattern of all females provide evidence of complex spatial structure and dynamics that encompasses both the open ocean and heavily fished coastal areas, and highlights the challenge of assessing and managing the porbeagle stock in this area.